Tinjauan Literatur Sistematis tentang Simulasi Sistem Antrean di Rumah Sakit: Model, Aplikasi, dan Evaluasi Kinerja - Latief Naufal Andryanto (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This systematic literature review examines queue system simulation in hospitals across four key service areas: emergency departments, outpatient clinics, laboratories, and pharmacies. Following PRISMA methodology, 72 relevant studies (2015-2020) were analyzed to identify simulation models, software tools, performance parameters, and emerging trends. Findings reveal Discrete-Event Simulation dominance (59.7%), with increasing hybrid model adoption integrating System Dynamics and Agent-Based approaches. Emergency departments remain the primary application focus (52.8%), while Arena and AnyLogic emerged as predominant simulation platforms. Patient waiting time (91.7%) and resource utilization (77.8%) constitute the most evaluated performance metrics. Technological convergence trends demonstrate integration of real-time data analytics, machine learning, and digital twin concepts into traditional simulation frameworks. This review contributes methodological insights for optimizing hospital queueing systems while identifying research gaps in cross-departmental model interoperability and comprehensive value-based performance evaluation within contemporary healthcare systems.